2023
DOI: 10.2147/nss.s391802
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fitbit Inspire 2TM Against Polysomnography in Adults Considering Adaptation for Use

Abstract: Purpose The commercialization of sleep activity tracking devices has made it possible to manage sleep quality at home. However, it is necessary to verify the reliability and accuracy of wearable devices through comparison with polysomnography (PSG), which is the standard for tracking sleep activity. This study aimed to monitor overall sleep activity using Fitbit Inspire 2™ (FBI2) and to evaluate its performance and effectiveness through PSG under the same conditions. Patients and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Lastly, while wearable devices like Fitbit offer valuable sleep metrics, their reliability should be approached with caution as many studies have attempted to validate Fitbit's sleep measures by comparing them with polysomnography. 74 77 Nonetheless, in the case of the Fitbit Inspire 2, the model used in this study, recent comparisons with polysomnography revealed no significant differences in SE, TIB and WASO, although it significantly overestimated TST. 74 …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Lastly, while wearable devices like Fitbit offer valuable sleep metrics, their reliability should be approached with caution as many studies have attempted to validate Fitbit's sleep measures by comparing them with polysomnography. 74 77 Nonetheless, in the case of the Fitbit Inspire 2, the model used in this study, recent comparisons with polysomnography revealed no significant differences in SE, TIB and WASO, although it significantly overestimated TST. 74 …”
Section: Discussionmentioning
confidence: 56%
“… 74 77 Nonetheless, in the case of the Fitbit Inspire 2, the model used in this study, recent comparisons with polysomnography revealed no significant differences in SE, TIB and WASO, although it significantly overestimated TST. 74 …”
Section: Discussionmentioning
confidence: 56%
“…This device estimates sleep stages by analyzing patterns of movement and heart rate, determining sleep when there is no movement detected for approximately one hour ( 22 ). Prior research on this device has indicated it to have high sensitivity (93.9%) and accuracy (76%), and its use as an objective tool for measuring sleep in daily life is considered appropriate ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Objective wearable data was collected passively from the Fitbit Inspire 2 device, which uses a triaxial accelerometer to measure ambulatory movement and estimate sleep (Lim et al, 2023). Devices were distributed via priority courier.…”
Section: Commercial Sleep Trackermentioning
confidence: 99%